Metodología para una auditoría financiera a la cuenta de efectivo de la empresa Skema Promotora S.A - Egas Botina, Leidy Dayana; Romo Melo, Lilybeth Carolina (Universidad Antonio Nariño, 2023)
The review assignment made to the company Skema Promotora S.A. Its main objective is to analyze through an audit methodology based on international standards (NIAS) the cash item in relation to the financial statements of December 31, 2022.